2008
DOI: 10.1089/dis.2008.1120007
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Barriers to Hypertension Care: Implications for Quality Improvement Initiatives

Abstract: The role of clinical inertia in the treatment of patients with hypertension was assessed by evaluating health care providers' knowledge, attitudes, and clinical practices regarding hypertension management. A cross-sectional survey was conducted at the Forsyth Medical Group in North Carolina. Participants were physicians (N = 18, 10 sites) and support staff (N = 20, 12 sites), who were surveyed in 2006. Physician and support staff questionnaires consisted of 29 and 15 items, respectively, and were administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 8 publications
(16 reference statements)
1
34
0
2
Order By: Relevance
“…When evaluating quintiles of therapeutic inertia, we observed that the quintile with the lowest therapeutic inertia achieved 75% control rates during the following year, whereas patients in the quintile with the highest therapeutic inertia achieved only 8% control rates [25]. Although patient nonadherence is cited by physicians as a reason not to intensify therapy [27], BP often declines when therapy is intensified, even in patients perceived to be less adherent [26 ].…”
Section: Therapeutic Inertiamentioning
confidence: 99%
See 2 more Smart Citations
“…When evaluating quintiles of therapeutic inertia, we observed that the quintile with the lowest therapeutic inertia achieved 75% control rates during the following year, whereas patients in the quintile with the highest therapeutic inertia achieved only 8% control rates [25]. Although patient nonadherence is cited by physicians as a reason not to intensify therapy [27], BP often declines when therapy is intensified, even in patients perceived to be less adherent [26 ].…”
Section: Therapeutic Inertiamentioning
confidence: 99%
“…Physicians are not confident of the validity of BP values recorded by their office staff [28]. This uncertainty, in turn, reduces the likelihood that action will be taken in response to an elevated reading [27,28]. Thus, the real and perceived inaccuracy in measuring office BP, combined with the substantial likelihood of a white coat or office effect on BP, reduces the likelihood that providers will intensify treatment in response to an elevated value.…”
Section: Therapeutic Inertiamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that encouragement by physicians can help to enhance patient compliance. 8,26,27 Patients perceive their physicians as a "very/extremely" useful source of information, 28 and thus a third component of our intervention focused on improving patient knowledge. 29 The last component of our multifaceted intervention addressed the educational needs and time demands of our nursing staff.…”
Section: Summary Of the Experience Future Directions And Challengesmentioning
confidence: 99%
“…The belief that inaccurate BP measurements are obtained by clinical staff is common among physicians; meanwhile, support staff report being rushed while measuring BPs, and many request BP competence training. 26 We constructed our intervention to address both of these needs.…”
Section: Summary Of the Experience Future Directions And Challengesmentioning
confidence: 99%